Eurocrime! : the Italian cop and the gangster films that ruled the 70s - Malloy, Mike, 1976-; Stielstra, Aaron (Subgenre Entertainment, LLC, 2012)
A documentary concerning the violent Italian 'poliziotteschi' cinematic movement of the '70s which, at first glance, seems like just a bunch of cheap rip-offs of American crime films like Dirty Harry or The Godfather. But on closer inspection, these films were really addressing distinctly Italian issues like the Sicilian Mafia and red terrorism.